2018
DOI: 10.9767/bcrec.14.1.2507.79-92
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Synthetic Zinc Oxide Catalyst over Nano-Alumina for Sulfur Removal by Air in a Batch Reactor

Abstract: Owing to the environmental regulations with respect to sulfur content and continuing challenges of finding a suitable catalyst of such impurity, a driving force for the development of more efficient technologies a deep research on new oxidative catalysts is considered an important issue in fuel quality improvement. Thus, the present study shows a novel percent of nano-catalyst with 18% zinc oxide (ZnO) of active component over nano-alumina that has not been reported in the public domain for sulfur removal from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Another study stated that the increment of the catalytic activity of ZnO can be corresponded to a lower band gap value (3.35 eV) compared to 3.65 eV for Zn5(OH)8Cl2•H2O, which would increase the absorption capacity of higher wavelength radiation [10]. A novel percent of nano-catalyst with 18% zinc oxide (ZnO) was an active component over nano-alumina for sulfur removal from kerosene fuel by air (oxidative desulfurization (ODS) method) [11]. Riad and Mikhail showed that Zn-incorporated hydroxyapatite catalysts were investigated towards oxidative desulfurization of light gas oil with a total sulfur content of 1281.8 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Another study stated that the increment of the catalytic activity of ZnO can be corresponded to a lower band gap value (3.35 eV) compared to 3.65 eV for Zn5(OH)8Cl2•H2O, which would increase the absorption capacity of higher wavelength radiation [10]. A novel percent of nano-catalyst with 18% zinc oxide (ZnO) was an active component over nano-alumina for sulfur removal from kerosene fuel by air (oxidative desulfurization (ODS) method) [11]. Riad and Mikhail showed that Zn-incorporated hydroxyapatite catalysts were investigated towards oxidative desulfurization of light gas oil with a total sulfur content of 1281.8 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…H2S (hydrogen sulfide) and carbon-sulfur components (such as CS2 and COS) are toxic byproducts of refining natural gas and crude oil, and therefore, their entrance in any exhaust gas is under stiff environmental regulations [1,2]. To tackle with this issue, the modified sulfur re-covery unit (SRU) is cherished to convert H2S and carbon-sulfur compounds coming from the exhaust of those industries to the elemental sulfur [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Claus process is conducted at two steps including thermal and catalytic stages [5]. The catalytic reactors of a SRU is usually loaded by alumina (Al2O3) and titania (TiO2) Claus catalysts (combined bed or multilayer configuration) to promote the following reactions [6,7]: Copyright © 2020, BCREC, ISSN 1978-2993 (1) (2) (3) Industrial scale reactors usually work adiabatically, and they are essentially different from bench or even pilot scale reactors. In the former, there is a temperature profile along the catalytic bed whereas in the latter a constant temperature governs the whole bed.…”
Section: Introductionmentioning
confidence: 99%
“…A number of oxidants are used in the ODS that have been employed for the selective oxidation of sulfur compounds in oil feedstock [14][15][16][17]. In order to improve the efficiency of sulfur removal in the ODS via using air as an oxidant, various catalysts have been evaluated including Al2O3-zeolite [18], Nano-Fe3O4 [19], -MnO2 (Nano sheets) [20], alumina [21], carbon Nano tube [20] and silica gel [19] found to enhance the desulfurization efficiency of the ODS process.…”
mentioning
confidence: 99%
“…A large quantity of sulfur compound are enhanced by the use of an oxidizing agent compared with traditional agent (hydrogen peroxide) [21]. The oxidative desulfurization process has been applied by [4] for sulfur compounds presented in naphtha feedstock using 0.1 wt% of palladium/functionalized MWNTs prepared by impregnation method.…”
mentioning
confidence: 99%